2020
DOI: 10.1002/essoar.10504066.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating Catchment Models as Multiple Working Hypotheses: on the Role of Error Metrics, Parameter Sampling, Model Structure, and Data Information Content

Abstract: KGEss is a more reliable metric than NSE and WIA, due to its mathematical structure.• The choice of error metricother things being equalchanges how model performance, parameter sampling sufficiency, and/or model hypotheses are measured.• Relying on large samples of parameter space, without considering the model solution space, is a major source of uncertainty.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 95 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…We also note that hydrological modellers are usually interested in low or high quantiles of streamflow. Although the model's structure can be customised to target such quantities, it is frequent to combine the model with a loss function suitable for modelling means (e.g., the squared error function or the Nash-Sutcliffe efficiency [88,89]). In such cases, one should not expect to obtain reliable estimates of quantiles of the predictive distribution, but rather customised estimates of the mean flow at low or high flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that hydrological modellers are usually interested in low or high quantiles of streamflow. Although the model's structure can be customised to target such quantities, it is frequent to combine the model with a loss function suitable for modelling means (e.g., the squared error function or the Nash-Sutcliffe efficiency [88,89]). In such cases, one should not expect to obtain reliable estimates of quantiles of the predictive distribution, but rather customised estimates of the mean flow at low or high flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For A = KGE with KGEpref = 1 and benchmarked against observed mean Aref = KGE(O̅ ) = 1-√2, the KGE skill score (KGEss) derives as below: (Khatami et al, 2020; i.e. Chapter 4 of this thesis).…”
Section: = − −mentioning
confidence: 99%
“…[-] developed the Kling-Gupta Efficiency (KGE) metric. We previously derived its skill score version ( ) and demonstrated that is a better metric than other conventional metrics like Nash-Sutcliffe efficiency and Willmott's refined index of agreement (Khatami et al, 2020). compares the distance between the time series of observed and modeled flows ( and ) against the overall observed mean ̅ : ( , , ̅ ).…”
Section: %] 16 P Skewnessmentioning
confidence: 99%
See 2 more Smart Citations